Applying dialectical behaviour therapy to structural and internalized stigma with LGBTQ+ clients. (10th January 2019) - Skerven, Kim; Whicker, Dane R.; LeMaire, Kelly L.
Abstract: Delivering research-supported intervention is increasingly important, given the growing emphasis on evidence-based practice in mental health treatment. When working with clients who hold marginalized identities, however, therapists may have questions about how to best tailor interventions, as treatments may not yet have demonstrated efficacy with under-represented populations. This paper describes potential strategies for using dialectical behaviour therapy (DBT) skills to help LGBTQ+ clients, guided by a theoretical model for understanding sexual stigma. Joining these two paradigms, suggestions are made for applications of skills that can help LGBTQ+ clients who are in DBT effectively interact with invalidating environments characterized by structural stigma. DBT-based strategies aimed at buffering clients from environmental invalidation and enhancing their skills in self-validation can help provide them with pathways towards affirming their own sexual orientation and gender identity. Examples from clinical cases are used to enhance understanding of skills application in practice.